2018
DOI: 10.1111/exd.13535
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells in autoimmune skin diseases

Abstract: Abstractautoimmune skin disorders, including alopecia areata, vitiligo, pemphigoid and pemphigus, and systemic sclerosis, and discusses questions that remain to be addressed. K E Y W O R D Salopecia areata, pemphigoid, pemphigus, systemic sclerosis, vitiligo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 64 publications
(81 reference statements)
0
38
0
1
Order By: Relevance
“…Decreasing in frequency and function of regulatory T cells has been well documented in autoimmune skin disorders which is accompanied with inhibition of peripheral tolerance. In this regard, the reduction in TGF‐β serum level has also been indicated in patients with vitiligo . Multiple immune checkpoint molecules are involved in these peripheral tolerance mechanisms to hamper and regulate the excessive inflammatory responses and autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing in frequency and function of regulatory T cells has been well documented in autoimmune skin disorders which is accompanied with inhibition of peripheral tolerance. In this regard, the reduction in TGF‐β serum level has also been indicated in patients with vitiligo . Multiple immune checkpoint molecules are involved in these peripheral tolerance mechanisms to hamper and regulate the excessive inflammatory responses and autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, they suggested that ST18 gene may increase susceptibility to PV among the selected population . ST18 gene encodes a zinc‐finger DNA‐binding protein which is involved in apoptosis, inflammation regulation, as well as regulatory T cells, as two processes which are involved in PV pathogenesis . In another study on Chinese population, no association was reported between ST18 gene and PV, more in favour of population‐specific manner susceptibility hypothesis .…”
Section: Introductionmentioning
confidence: 99%
“…[10] ST18 gene encodes a zinc-finger DNA-binding protein which is involved in apoptosis, inflammation regulation, [11] as well as regulatory T cells, as two processes which are involved in PV pathogenesis. [12][13][14] In another study on Chinese population, no association was reported between ST18 gene and PV, more in favour of population-specific manner susceptibility hypothesis. [15] Recently, PV-associated variants within ST18 promoter region were discovered to increase ST18 transcription which subsequently induced inflammatory cytokines and contributed to PV pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism of action of the immune‐modulating effect in DPCP is unclear, but to date it is generally assumed that it acts on different pathways to inhibit inflammation in alopecic areas which is achieved mainly by suppression of inflammatory cells, such as CD4+ and CD8+ T cells, restoration of equilibrium between Th1 and Th2 responses, or involvement of regulatory T cells . In our study, post‐treatment levels of serum Th1 type cytokines IFN‐γ and IL‐12 were significantly decreased, and levels of serum Th2 type cytokines IL‐4 and IL‐10 were increased in the responder group, which was different from the non‐responder group.…”
Section: Discussionmentioning
confidence: 48%